Respuesta :

Answer:

2) x = -4; y = 0; z = -2

4) x = 4; y = 2; z = 0

Step-by-step explanation:

2)

-4x - 5y - z = 18

-2x - 5y - 2z = 12

-2x + 5y + 2z = 4

Add the 2nd and 3rd equations to eliminate y and z.

-4x = 16

x = -4

Substitute x = -4 in first and second equations.

(-4)(-4) - 5y - z = 18

(-2)(-4) - 5y - 2z = 12

-5y - z = 2

-5y - 2z = 4

Multiply first equation by -1 and add to second equation.

       5y + z = -2

(+)   -5y - 2z = 4

----------------------

               -z = 2

z = -2

Substitute x = -4 and z = -2 in first original equation and solve for y.

-4(-4) - 5y - (-2) = 18

16 - 5y + 2 = 18

-5y = 0

y = 0

Answer: x = -4; y = 0; z = -2

4)

4x + 4y + z = 24

2x - 4y + z = 0

5x - 4y - 5z = 12

Add equations 1 and 3 to eliminate y.

9x - 4z = 36    Eq. 1

Add equations 1 and 2 to eliminate y.

6x + 2z = 24    Eq. 2

Multiply Eq. 2 by 2 and add to Eq. 1.

       12x + 4z = 48

(+)      9x - 4z = 36

----------------------------

        21x       = 84

x = 4

Substitute x = 4 into Eq. 1 to solve for z.

9x - 4z = 36

9(4) - 4z = 36

-4z = 0

z = 0

Substitute x = 4 and z = 0 into the first original equation to solve for y.

4x + 4y + z = 24

4(4) + 4y + 0 = 24

4y = 8

y = 2

Answer: x = 4; y = 2; z = 0